ANALISIS PENGARUH NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO, CAPITAL ADEQUACY RATIO, DAN LEVERAGE MULTIPLIER TERHADAP PROFITABILITAS (Studi Penelitian Pada Perusahaan Perbankan Yang Terdaftar Dalam Bursa Efek Indonesia Tahun 2011-2014) - Bayu Widiyanto, 11.05.52.0183; Lisiantara, Anggana (Students Journal of Accounting and Banking, 2016)
This research was conducted to test the influence of Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Leverage Multiplayer (LM), the Capital Adequacy Ratio (CAR) of profitability (Return On Assets). The sample in this study were 27 banking company went public during the period of the year 2011 to 2014.Â Methods of analysis used in this research is by using multiple linear regression analysis. Multiple regression analysis is used to test whether there is influence of the NPL, LDR, LM, and CAR against profitability (ROA). Multiple linear regression analysis can also be used to test whether there is influence among variables and time dummy dummy bank towards profitability (ROA).Â The results of this study indicate that, of Non Performing Loan (NPL) is the variable that affects the profitability of the bank (ROA). While the time dummy, this research suggests that there may be differences in profitability between years occurred in the fourth year (2014), and to demonstrate that the banks dummy order banks to 9 (PT Bank Rakyat Indonesia) had differences with other bank profitability.Keywords: NPL, LDR, LM, CAR